Elevated activity levels do not influence extrinsic fiber attachment morphology on the surface of muscle‐attachment sites. Issue 5 (16th December 2019) - Turcotte, Cassandra M.; Green, David J.; Kupczik, Kornelius; McFarlin, Shannon; Schulz‐Kornas, Ellen
Abstract: Extrinsic fibers (EFs) are a type of penetrating collagenous fiber, closely related to the periodontal ligament, which help anchor soft tissue into bone. These fibers are associated with muscle attachment sites (entheses). Their size and grouping patterns are thought to be indicative of the loading history of the muscle. EFs are of particular significance in anthropology as potential tools for the reconstruction of behavior from skeletal remains and, specifically, entheses. In this study, we used a mouse model to experimentally test how activity level alters the morphology of EF insertion sites on the bone surface of a fibrocartilaginous enthesis, the biceps brachii insertion. Further, we adapted surface metrological techniques from studies of dental wear to perform automated, quantitative and non‐destructive analysis of bone surface histology. Our results show that experimentally increased activity had no significant effect on the quantity or density of EF insertions at the enthesis, nor on the size of those insertions. Although EF presence does indicate muscle attachment, activity did not have an observable effect on EF morphology. Abstract : This study adapts surface metrological techniques to the automated, quantitative and non‐destructive analysis of bone surface histology. Although extrinsic fiber (EF) presence does indicate muscle attachment, activity does not have an observable effect on EF morphology.